Veterans' Experiences of an Opioid Specialty Clinic. Issue 10 (9th March 2021) - Sowicz, Timothy Joseph; Hausmann, Leslie R M
Abstract: Objective: Opioid specialty clinics have emerged as an approach for mitigating the risks associated with opioid therapies. Many opioid specialty clinics within the Department of Veterans Affairs (VA) have been described in the extant literature, yet veterans' experiences of these remain absent. This research study was undertaken to describe veterans' responses (e.g., knowledge, attitudes, and beliefs) toward being evaluated in an opioid specialty clinic. Design: Qualitative descriptive research study. Setting: A VA medical center in the northeast United States. Subjects: Twenty veterans were interviewed between December 2017 and May 2018. Methods: Veterans' characteristics were extracted from the VA's electronic health record and analyzed with descriptive statistics. Qualitative data about veterans' experiences with the opioid specialty clinic were collected via semistructured interviews (in person or via telephone) and were analyzed with qualitative content analysis. Results: Most participants were older, non-Hispanic or non-Latino white men. Generally, veterans had positive experiences in the opioid specialty clinic. However, there was wide variation in their understanding of the purpose of the clinic, who staffed the clinic, and why they had been referred to the clinic. Conclusions: For veterans prescribed opioid therapies, this clinic served as an adjunct service for ensuring appropriate and safe prescribing. Data from this study can be used to inform interventions to promote veterans' understanding across the total opioid safety clinic experience—referral, actual visit, and follow-up.